Origin and evolution of fault-controlled hydrothermal dolomitization fronts: a new insight - Koeshidayatullah, Ardiansyah; Corlett, Hilary; Stacey, Jack; Swart, Peter K.; Boyce, Adrian; Hollis, Cathy (My University, 2020)
Dolomitization is one of the most significant diagenetic reactions in carbonate systems, occurring where limestone (CaCO3) is replaced by dolomite (CaMg (CO3)2) under a wide range of crystallization temperatures and fluids. The processes governing its formation have been well studied, but the controls on the position of dolomitization fronts in ancient natural settings, particularly in a fault-controlled hydrothermal system (HTD), have received remarkably little attention. Hence, the origin and evolution of HTD dolomitization fronts in the stratigraphic record remain enigmatic. Here, a new set of mineralogical and geochemical data collected from different transects in a partially dolomitized Cambrian carbonate platform in western Canada are presented to address this issue. Systematic patterns of sudden decrease in the magnesium content (mol% MgCO3) and increase in porosity were observed towards the margin of the body. Furthermore, fluid temperatures are cooler and Owater values are less positive at the dolomitization front than within the core of the body. These changes coincide with a change from poorly ordered, planar-e dolomite with multiple crystal zonations at the margin, to an unzoned, well-ordered, interlocking mosaic of planar-s to nonplanar dolomite in the core of the body. These phenomena are hypothesized to reflect dynamic, self-limiting processes in the formation and evolution of HTD dolomitization fronts through (i) plummet of dolomitization potential at the head of dolomitizing fluids due to progressive consumption of magnesium and fluid cooling; and (ii) retreat of dolomitization fronts towards the fluid source during subsequent recrystallization of the dolomite body, inboard of the termination, once overdolomitization took place. This new insight illustrates how dolomitization fronts can record the oldest phase of dolomitization, instead of the youngest as is often assumed. Formation of porosity is interpreted to occur as the result of acidification-induced grain leaching during the development of dolomitization fronts. This mechanism, coupled with retrogradation of dolomitization fronts, may help to explain the apparent enhancement of porosity in proximity to dolomitization fronts.
Keywords: dolomitization fronts; hydrothermal; Mg/Ca ratio; recrystallization; retreat; self-limiting